Promieniowa zmienność właściwości drewna sosny zwyczajnej (Pinus sylvestris L.) wyrosłej na gruntach porolnych - Tomczak, Arkadiusz; Jelonek, Tomasz (Leśne Prace Badawcze, 2013)
The soil of former farmland greatly differs from forest soil, and significantly influences tree growth and development compared with other site factors. The effect may also be reflected indirectly in radial variability of wood. This study compared radial variation of wood density, compressive strength along the grain and static bending strength of wood of Scots pine trees growing on former farmland and forest soils. The analyses were conducted in eight mature pine stands. On the basis of the stand description, four stands were classified as growing on forest soil (L) and four as growing on former farmland soil (P). A total of 24 model trees were selected, twelve on each soil type. Analyses of wood properties were conducted along four axes from the cross sectional radius of the treesat breast height. Our analyses showed that radial variation in wood properties of Scots pine (from selected locations in Poland) growing on former farmland is similar to the variation among the control trees growing on forest soils. In both groups of trees, the lowest density and the lowest strength were in the pith (juvenile) zone. Wood with the highest density and greatest strength was located in the central part of the radius. Wood of Scots pine trees growing on former farmland soils in comparison to that of trees growing on forest soil was characterised by a statistically lower basic density, lower compressive strength along the grain and static bending strength.